Removal of 26 corticosteroids, potential COVID-19 remedies, at environmentally relevant concentrations in water using UV/free chlorine, UV/monochloramine, and UV/hydrogen peroxide - Zhang, Ai (2022)
As a class of endocrine disrupting compounds (EDCs), corticosteroids (CSs) have attracted increasing attention due to their large excretion masses and toxic effects. However, compared to the very well-studied estrogens and androgens, few studies have been made dealing with the removal of CSs at environmentally relevant concentrations using advanced water and wastewater treatment processes. In this study, degradation performances of 26 natural and synthetic CSs in secondary effluent at environmentally relevant concentrations were comparatively investigated during UV/free chlorine (UV/Cl2), UV/monochloramine (UV/NH2Cl) and UV/hydrogen peroxide (UV/H2O2) treatments. The 26 CSs could be divided into two groups: UV sensitive CSs, which have two double bonds in ring A (Δ1,4), and UV insensitive CSs, which have only one double bond in ring A (Δ4). The UV sensitive CSs could be effectively removed (removal efficiency >60%) by a UV dose of 100 mJ cm−2 while the UV insensitive CSs could be removed (removal efficiency >40%) by a UV dose of 800 mJ cm−2. The removal efficiencies of UV insensitive CSs increased with the increase of UV dose. Most of the CSs were poorly removed by sole Cl2, NH2Cl, or H2O2 treatment (removal efficiency <40%). However, the addition of Cl2, NH2Cl, and H2O2 promoted the UV degradation of CSs, especially for UV-insensitive CSs. UV photolysis would be the predominant mechanism in the UV/Cl2, UV/NH2Cl, and UV/H2O2 processes for removing CSs in water. Besides the UV photolysis, HO˙ radicals also functioned for CS removal. Compared with the insignificant effects of reactive chlorine species (RCS), the reactive nitrogen species (RNS) showed obvious selectivity in CS degradation. This study expanded the UV induced oxidation performances of CSs, which lays a foundation for exploring degradation mechanisms and eliminating the pollution from CSs.